Criteria used by mathematics teachers to pose problems in the classroom - Pino-Fan, Luis R. (2020)
The study of the problems posed by teachers to their students and the characteristics that should be considered to enhance mathematical competences is an issue that has gained interest in recent years. However, most of these studies have been approached from an epistemic, technological, or cognitive point of view, without effectively considering what math teachers usually do to pose problems in their classes. In this sense, the objective of this article is to explore the pedagogical conceptions and practices of a group of elementary and secondary teachers from southern Chile about the selection of mathematical problems for their classes, and the criteria they use for such selection. The interest of this study stems from assuming that, in the classroom, teachers are the articulating vehicle of educational policies. Another motivation for this paper is the results of research in Mathematics Education. For this purpose, a questionnaire was presented which showed that teachers choose any of the following three mathematical problems: i) problems taken from textbooks, internet, and other resources; ii) problems adapted from textbooks, internet, or other resources (own variations); and iii) problems created by the teacher. In any case, there is a growing interest in teachers to pose problems with contexts that students feel close to and arouse interest from an emotional point of view. In addition, it was observed that the criteria used by teachers for posing math problems in the classroom implicitly contemplate the didactical suitability criteria proposed within the framework of the Onto-Semiotic Approach to Mathematical Knowledge and Instruction (OSA).